Hamiltonian Analysis and Dual Vector Spectral Elements for 2D Maxwell Eigenproblems (Communications in Computational Physics, 2018)
The 2D Maxwell eigenproblems are studied from a new point of view. Anelectromagnetic problem is cast from the Lagrangian system with single variable intothe Hamiltonian system with dual variables. The electric and magnetic componentstransverse to the wave propagation direction are treated as dual variables to each other.Higher order curl-conforming and divergence-conforming vector basis functions areused to construct dual vector spectral elements. Numerical examples demonstratesome unique advantages of the proposed method.